PENGARUH PENERAPAN GENIALLY TERHADAP HASIL BELAJAR SISWA KELAS III SD MUHAMMADIYAH PADA MAKNA SILA PANCASILA - Dewi, Alicia Fitria; Alfin, Apilia Halisa; Muyessaroh, Aris; Rania, Nabila Putri; Maryani, Nurul; Karim, Ahmad Syafii; Rahmawati, Ika Dian (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The objective of this study is to evaluate the significance of Pancasila principles to students who are in third grade at SD Muhammadiyah 1 Bangkalan by using Genially, an interactive web-based learning platform. The background of this study is the persistent problem that students have with understanding of Pancasila values, mostly memorizing them rather than internalizing them in their daily lives. A quantitative approach with a one-group pretest-posttest experimental design, data were collected through tests, documentation, and observation. Purposive sampling was used to choose class III A students for the sample. Student’s scores before and after the intervention were compared statistically using the. With rising and result showing a significance value of 0.000 < 0.05, the results demonstrated a significant increase in the learning outcomes of the pupils. This demonstrates that students' comprehension of Pancasila was positively and statistically significantly impacted by the use of Genially. study's findings, Genially is a successful teaching tool that improves motivation, engagement, and conceptual learning. As a result, it supports the use of digital technology in primary-level civic education.